Agent-based macroeconomics - a baseline model - Matthias Lengnick (Kiel University, Department of Economics, 2011)
This paper develops a baseline agent-based macroeconomic model and contrasts it with the common dynamic stochastic general equilibrium approach. Although simple, the model can reproduce a lot of the stylized facts of business cycles. The author argues that agent-based modeling is an adequate response to the recently expressed criticism of macroeconomic methodology. It does not depend on the strict assumption of rationality and allows for aggregate behavior that is more than simply a replication of microeconomic optimization decisions. At the same time it allows for absolutely consistent micro foundations. Most importantly, it does not depend on equilibrium assumptions or fictitious auctioneers and does therefore not rule out coordination failures, instability and crisis by definition.
Keywords: B4; E1; E50; 330; agent-based modeling; complex adaptive systems; microfoundations of macroeconomics